Perceptions of Legal and Extralegal Punishments for Sexual Harassment in the 'MeToo' Era. Issue 7 (3rd July 2021) - Nodeland, Brooke; Craig, Jessica
ABSTRACT: The current study investigates a sample of American university students' (n = 304) perceptions of legal and extralegal punishments for Kevin Spacey, Matte Lauer, and Roy Moore in the initial days of the 'MeToo' movement. Specifically, we examine the impact of respondent gender to determine if the 'MeToo' movement has changed the discrepancy in perceived seriousness between males and females. Being female and having knowledge of the allegations against the individual in each case significantly increased the odds of support for punishment. Findings are discussed in the cultural context of 'MeToo.'